Financial Management Of Mosques Based On Sharia Financial Management By The Leadership Of The Muhammadiyah Batang Branch - Fityani Amalia; Hery Purwanto (UP2MF Fakultas Ekonomi dan Bisnis, Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2025)
Mosques are places of worship for Muslims worldwide. Besides their function as places of worship, mosques also serve as a means of developing the Muslim community's economy. The openness of mosques in providing information about their funds often serves as a model for other institutions. For example, in managing mosque finances, the community is informed of the amount of incoming and outgoing funds. Through this transparency, it is not uncommon to see mosque funds reaching significant amounts, prompting many mosques to strive to utilize these funds productively to support the economic development of the community. A problem that arises when mosques seek to utilize their funds productively is the lack of knowledge among mosque administrators (nazir) in managing mosque finances based on Sharia-compliant financial management. However, by recognizing the mosque's financial potential, mosques can actually facilitate community business development or provide capital under Sharia-compliant systems. This is the goal of this community service program, where the organizers will provide training to mosque administrators on Sharia-compliant financial management, enabling mosques to utilize their funds productively and contribute to the economic development of the community surrounding the mosque.